A novel optical network modelfor network burden release and congestion reduction based onpassive optical network. (October 2018) - Li, He; Yin, Hongxi; Lin, Shanshan
In this article, a new optical network structure coping with network congestion is proposed, which is based on passive optical network, and adopts data storage devices coupled with optical line terminal to release network burden. It is shown by our network performance simulation that this network has many merits such as free-scale, fewer connections, larger clustering coefficient, and smaller average shortest path length in comparison to the passive optical network. The novel network structure can replace the far-end service connections with the near-end ones, reduce congestions in an optical network, and, furthermore, relieve traffic burden in optical backbone and metropolitan area networks.